Penerapan Zona Halal untuk Bahan Mentah Berskala Mikro: Model Strategis dan Tantangan di Tingkat Lokal - Julian Azhari, Fajar; Mulyana, Andri; Aufi, Irwan; Rochim, Abdul; Muhammad Zikril Hakim, Ade (Pusat Riset dan Inovasi Nasional, 2025)
The halal zone is a crucial component in the halal supply chain, ensuring compliance with Sharia standards from the raw material stage. This study examines the implementation of halal zones for micro-scale raw materials by highlighting strategic models and challenges at the local level. The objective of this research is to explore effective strategies for establishing halal zones that cater to the needs of small and medium-sized industries while identifying barriers to their implementation. The study employs a literature review method by analyzing recent literature on the halal supply chain, halal regulations, and relevant case studies. The findings reveal that the successful implementation of halal zones largely depends on the synergy between business actors, local governments, and halal certification bodies. The main challenges include a lack of awareness among business owners regarding halal principles, limited supporting infrastructure, and the complexity of the certification process. The implications of this research emphasize the need for more adaptive policies and community-based support systems to accelerate the adoption of halal zones at the local level. With the right strategy, halal zones can enhance the competitiveness of the halal industry and strengthen consumer trust in Sharia-compliant products.